2016
DOI: 10.1093/femsec/fiw134
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the interactions among microbial populations found in activated sludge during biofilm formation

Abstract: Microorganisms colonize surfaces and develop biofilms through interactions that are not yet thoroughly understood, with important implications for water and wastewater systems. This study investigated the interactions between N-acyl homoserine lactone (AHL)-producing bacteria, yeasts and protists, and their contribution to biofilm development. Sixty-one bacterial strains were isolated from activated sludge and screened for AHL production, with Aeromonas sp. found to be the dominant AHL producer. Shewanella xia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…250 Hence, the benet of a newly established cooperation needs to outweigh the negative effect of conicts and increased competition in local groups of cells. Importantly, the formation of biolms and cell clusters can be caused by a number of non-social reasons, such as the protection from the abiotic (oxygen, pH, and drought) and biotic environment (predation, 251,252 competition, and immune system), colonisation of favourable substrates (energy-and carbon-sources), or joint niche construction and exploitation (synergism). 253 Once established, several important consequences result for cells that grow in spatially structured communities.…”
Section: Evolution Of Cooperative Cross-feedingmentioning
confidence: 99%
“…250 Hence, the benet of a newly established cooperation needs to outweigh the negative effect of conicts and increased competition in local groups of cells. Importantly, the formation of biolms and cell clusters can be caused by a number of non-social reasons, such as the protection from the abiotic (oxygen, pH, and drought) and biotic environment (predation, 251,252 competition, and immune system), colonisation of favourable substrates (energy-and carbon-sources), or joint niche construction and exploitation (synergism). 253 Once established, several important consequences result for cells that grow in spatially structured communities.…”
Section: Evolution Of Cooperative Cross-feedingmentioning
confidence: 99%
“…Furthermore, their biofilm behavior may also be governed by N-acyl homoserine lactone (AHL) quorum sensing (Liebana et al, 2016).…”
Section: Sludgementioning
confidence: 99%
“…Acinetobacter sp. has been reported as primary colonizers and bridging bacteria in aggregate/biofilm development (Katharios-Lanwermeyer et al, 2014, Liébana et al, 2016 and have previously been observed during initial stages of granulation (Weissbrodt et al, 2012). Acinetobacter sp.…”
Section: Succession Of Taxa During the Granulation Processmentioning
confidence: 80%